Kesesuaian Tata Guna Lahan Terhadap Penerapan Konsep Transit Oriented Development (TOD) di Kota Semarang - Arif, Firman Nur; Manullang, Okto Risdianto (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Land use development plan and integrated transport network in Semarang City requires planning based on the determination of the movement of transit. TOD (Transit Oriented Development) is a model for integration of transportation and land use in order to encourage the transit area. The purpose of this study was to determine the suitability of land use based on concept of TOD in Semarang City. The scope of the research areas at 8 of 10 BWK in Semarang City exclude BWK VI and BWK VIII. Data collection techniques are observation, survey and document review agencies. Analysis of data using a theoretical approach to the concept of TOD, further buffering analysis at point transit using GIS tools with a distance of 600 meters. Results of the research is a concordance rate land use on the application of concept TOD in Semarang City, as for the results 1,15% of 8 BWK were examined. Of the 8 BWK in detail there are only two BWK corresponding to BWK I (one TOD knot) percentage of 6.5% and BWK II (two TOD knots) percentage of 14.08%.